Enfortumab vedotin plus pembrolizumab for recurrent metastatic urothelial carcinoma following adjuvant nivolumab - Lan Inoki; Saizo Fujimoto; Mamoru Hashimoto; Yutaka Yamamoto; Teruo Inamoto; Keita Tamura; Takuhisa Nukaya; Kiyoshi Takahara; Wataru Fukuokaya; Takafumi Yanagisawa; Yuki Yoshikawa; Ryoichi Maenosono; et al. (Japanese Journal of Clinical Oncology, 2026)
Abstract Adjuvant nivolumab is an established postoperative treatment for high-risk urothelial carcinoma, but evidence for subsequent enfortumab vedotin plus pembrolizumab (EVP) after recurrence is limited. We retrospectively evaluated 17 patients with locally advanced or metastatic urothelial carcinoma who received EVP after recurrence following adjuvant nivolumab in a Japanese multi-institutional cohort. Among 16 response-evaluable patients, the objective response rate was 68.8% (11/16; exact 95% confidence interval [CI]: 41.3%–89.0%), including four complete responses and seven partial responses. Responses were observed across nivolumab-free interval groups. Median progression-free survival was 5.2 months (95% CI, 2.5-not estimable), and the median overall survival was not reached (95% CI, 8.4-not estimable). Grade 3 or higher adverse events occurred in three patients (17.6%), and one treatment-related death was recorded. These findings suggest clinically meaningful antitumor activity of EVP after recurrence following adjuvant nivolumab, warranting confirmation in larger comparative studies.